Petroleum Production – United States - Oil Production and Development in Oklahoma in 1928 - E. P. Hindes (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1929)
The total amount of oil produced in the state of Oklahoma during the year 1928 was 242,286,400 bbl., as compared to 273,372,650 bbl. in 1927; 177,650,000 bbl. in 1926; and 167,900,000 bbl. in 1925. The year 1928 ranks second to 1927 in which more oil was produced in the state than in any previous year. The large in in 1927 and 1928 was due principally to the development of the Greater Seminole district. The decrease of approximately 31,000,000 bbl. in the 1928 production as compared with the production in 1927, was caused by a drop of nearly 8,500,000 bbl. in the Seminole district production and a more or less normal decline in the production of practically all the other older and more settled fields. During 1928 approximately 1800 producing wells were drilled in Oklahoma, which yielded during the year approximately 90,000,000 bbl. of oil. The average initial production of these wells was 850 bbl. per day, and the average daily production per well for the year was 137 bbl. The average daily production per well of the total number of wells producing in 1928 was 10.9 bbl., which is a 13.5 per cent. decrease from the 1927 average of 12.6 barrels. At the close of 1928 a total of 95,400 producing wells had been drilled in the state, and approximately 61,000 were still producing. The grand total amount of oil produced in the state from the time the first well was drilled up to and including 1928 was 2,553,000,000 bbl. The production in 1928 was 9.5 per cent. of the total oil produced in the state. Texas led all other states in 1928, with a production of 251,835,200 bbl. Oklahoma was second with 242,286,400 bbl., and California was third with 231,982,600 barrels. Fields outside Greater. Seminole District Practically all the old settled fields in Oklahoma experienced a normal and expected decline during the year 1928. The fields showing the most, pronounced decline as compared to 1927 were: Burbank, which dropped from 15,230,400 to 11,939, 150 bbl.; Tonkawa, from 7,692,000 to 4,952,900 bbl.; Garber, from 5,056,300 to 3,139,400 bbl., and Wewoka, from 6,188,-800 to 2,450,400 bbl. There were no new extensions, discoveries of